Degradation dynamics and processes associated with the accumulation of Laminaria hyperborea (Phaeophyceae) kelp fragments: an in situ experimental approach. Issue 6 (11th August 2020) - de Bettignies, Florian; Dauby, Patrick; Thomas, François; Gobet, Angélique; Delage, Ludovic; Bohner, Olivier; Loisel, Stéphane; Davoult, Dominique
Abstract : A high proportion of the kelp Laminaria hyperborea production is exported from kelp forests following seasonal storms or natural annual old blade loss. Transport of drifting kelp fragments can lead to temporary accumulations in benthic subtidal habitats. We investigated the degradation processes of L. hyperborea in a low subtidal sandy bottom ecosystem by setting up a 6‐month cage experiment to simulate accumulations of kelp fragments on the seafloor. We monitored temporal changes in biomass, nutritional quality (C:N ratio), respiration, quantum efficiency of photosystem II ( F v / F m ), bacterial colonization, and chemical defense concentrations. Biomass decomposition started after 2 weeks and followed a classic negative exponential pattern, leading to 50% degradation after 8 weeks. The degradation process seemed to reach a critical step after 11 weeks, with an increase in respiration rate and phlorotannin concentration in the tissues. These results likely reflect an increase in bacterial activity and a weakening of the kelp cell wall. After 25 weeks of degradation, only 16% of the initial biomass persisted, but the remaining large fragments looked intact. Furthermore, photosystems were still responding to light stimuli, indicating that photosynthesis persisted over time. Reproductive tissues appeared on some fragments after 20 weeks of degradation, showing a capacity to maintain the reproductive function. Our results indicate that L. hyperborea fragments degrade slowly. As they maintain major physiological functions (photosynthesis, reproduction, etc.) and accumulate on adjacent ecosystems, they may play a long‐term ecological role in coastal ecosystem dynamics.